2021
DOI: 10.1038/s41419-021-04262-x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase (FASN) regulates the mitochondrial priming of cancer cells

Abstract: Inhibitors of the lipogenic enzyme fatty acid synthase (FASN) have attracted much attention in the last decade as potential targeted cancer therapies. However, little is known about the molecular determinants of cancer cell sensitivity to FASN inhibitors (FASNis), which is a major roadblock to their therapeutic application. Here, we find that pharmacological starvation of endogenously produced FAs is a previously unrecognized metabolic stress that heightens mitochondrial apoptotic priming and favors cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 88 publications
1
45
0
Order By: Relevance
“…Our data also provide evidence for a communication between fatty acid metabolism inside and outside of cancer cells. A recent study suggested that FASN inhibition increases mitochondrial priming and enhances breast cancer cell sensitivity to BCL2-targeting BH3 mimetics which may directly activate the apoptotic machinery and generate more potent and longer-lasting antitumor responses in a clinical setting 46 . We showed that OC cells are more resistant to the FASN inhibitor Cerulenin when they are cultured in the conditioned medium with higher POSTN.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also provide evidence for a communication between fatty acid metabolism inside and outside of cancer cells. A recent study suggested that FASN inhibition increases mitochondrial priming and enhances breast cancer cell sensitivity to BCL2-targeting BH3 mimetics which may directly activate the apoptotic machinery and generate more potent and longer-lasting antitumor responses in a clinical setting 46 . We showed that OC cells are more resistant to the FASN inhibitor Cerulenin when they are cultured in the conditioned medium with higher POSTN.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism has attracted significant attention in cancer research in recent years because it provides a novel connection between blockers of lipid metabolism and inhibitors of tumor growth and invasion [ 17 ]. FASN regulates fatty acid metabolism and plays a critical role in the growth and tissue invasion by many cancers [ 18 , 19 ]. We found a few studies providing deep analysis of the role of FASN in clear cell renal carcinoma development.…”
Section: Discussionmentioning
confidence: 99%
“…FASN is overexpressed in 70% of operable TNBC and is associated with poor prognosis [ 117 , 118 ]. FASN regulates Bcl-2 family proteins and controls breast cancer cell survival [ 119 ]. Acetyl-CoA synthetase 2 (ACSS2) is amplified in breast cancers and targeting ACSS2 impaired tumor growth in TNBC [ 120 , 121 ].…”
Section: Evidence That Mitochondria Are a Target In Breast Cancermentioning
confidence: 99%